A new Eulerian method to estimate "spicy" Agulhas leakage in climate models. Issue 11 (11th June 2015) - Putrasahan, D. A.; Beal, Lisa M.; Kirtman, Ben P.; Cheng, Yu
Abstract The Agulhas leakage brings warm and saline water from the Indian Ocean into the South Atlantic, forming part of the returning branch of the global thermohaline circulation, an important component of climate. We develop a new method using the passive tracer spice, to estimate Agulhas leakage transport in an ocean eddy‐resolving climate model that properly captures Agulhas Retroflection and leakage. We identify Agulhas leakage waters as positive spice anomalies (≥ +0.1) and are able to trace leakage to depths greater than 1000 m. Spice‐based Eulerian Agulhas leakage captures spikes in Lagrangian leakage transport which coincide with the passage of Agulhas rings, yielding a statistically significant correlation (0.47). On interannual times scales, differences between Eulerian and Lagrangian transports are reduced and correlation increases to 0.77. We obtain a mean spice‐based Eulerian Agulhas leakage of 17 ± 4 sverdrup (Sv) and Lagrangian Agulhas leakage of 18 ± 2 Sv, which are within the range of observational estimates.